2021
DOI: 10.3389/fpubh.2021.646494
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Catastrophic Health Expenditures on Chinese Household Consumption

Abstract: China has built a social medical insurance system that covers the entire population so as to reduce the impact of diseases on individuals and families. Although the decline in the incidence of catastrophic health expenditures (CHEs) in China is encouraging, this issue remains important. On the basis of considering selectivity bias and heterogeneity, we applied propensity score matching (PSM) to analyze the 2018 data from the China Family Panel Studies. We assigned CHE households and non-CHE households to the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
1
11
1
Order By: Relevance
“…The CBHI has decreased household per-capita health expenditure of the insured group by 17, 15, and 14 percentage points for nearest-neighbor, Kernel-based, and radius matching, respectively. This finding is similar to other studies ( 2 , 14 , 47 , 48 ).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The CBHI has decreased household per-capita health expenditure of the insured group by 17, 15, and 14 percentage points for nearest-neighbor, Kernel-based, and radius matching, respectively. This finding is similar to other studies ( 2 , 14 , 47 , 48 ).…”
Section: Resultssupporting
confidence: 93%
“…Different studies also support this; for example, the study by Wei et al ( 2 ) found that a percentage increment in the per-capita medical expenses of a household, the per-capita food consumption expenses of a household diminished by 7.6%, and also Leive and Xu ( 5 ) studied on 15 African countries, including Ethiopia, revealed that there was tradeoff relationship between health expenditure and consumption expenditure. Similarly, Shikuro et al ( 6 ) and Kiros et al ( 7 ) found that the catastrophic health expenditures on households were 21.5 and 22.5%, respectively, and such expenditures also devastate the consumption expenditures and social wellbeing.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…As for financial protection, most studies found that China's basic medical insurance didn't reduce the out-of-pocket health expenditure [4][5][6][7]. Since financial burden is not only associated with the out-of-pocket health expenditure but also associated with residents' capacity to pay, most studies used catastrophic health expenditure (CHE) as the indicator for financial protection [8][9][10][11][12][13]. Li et al [9] found that the poorest residents spent the least but their incidence of CHE was the highest.…”
mentioning
confidence: 99%
“…Take studies of the impact of health shocks on households' spending decisions as an example. Most studies find that the increased healthcare expenditures as a result of household members experiencing health shocks inevitably affect various aspects of household life, including the time allocation between work and leisure ( 12 ), consumption-savings ratio ( 13 ), and preference for investment risks ( 14 ), forcing the household to adjust their behaviors in making economic-related decisions ( 15 ) and ultimately creating a significant crowding-out effect on other household expenditures, such as income, labor supply, and education ( 16 ). This effect is more evident in rural households and households with a medium-level income ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%